Pengaruh Online Customer Review, Online Customer Rating, dan Price Consciousness terhadap Keputusan Pembelian - Wiwit Lestari; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to analyze whether there is an influence of online customer review, online customer rating and price consciosness on the study purchase decision of TikTok Shop customers. The population used in this study were TikTok Shop customers in Yogyakarta. This study uses a type of questionnaire that uses Google Form as a research tool. The research method used is a non-probability sampling technique with purpusive sampling method. The sample used is 100 respondents. The data obtained from the questionnaire was then processed and analyzed using Multiple Linear Regression analysis with model determination (classical assumption test), hypothesis testing using partial test (t) and determination test (R2) using SPSS 25 program. The results of this study indicate that the variable online customer review has no significant effect on purchasing decisions, online customer rating variable has no significant effect on purchasing decisions, price consciousness variable has a significant positive effect on purchasing decisions and online customer review, online customer rating, and price consciousness variables have a significant positive effect on purchasing decisions. Keywords: TikTok Shop, online customer review, online customer rating, price consciousness, purchase decision